(untitled) (Bangladesh Journal of Nutrition, 2015)
Linkages between diet habits and the quality of working life is a new phenomenon and continue to surface on many fronts. Evidences are there that dietary and non-dietary components are capable of influencing workplace activities, work life, and thereby work performance and productivity. This cross sectional study examined the quality of working life (QWL) and nutritional status of a representative group of sixty-five male workers in an industrial setting. Quality of work life index was measured by administering the scale developed by Yousuf. Nutritional status was assessed by 24-hr food recalls and anthropometric measures. The measured score for QWL ranged 185.0-212.0 with a mean of 193.83 ± 5.57, which is about seventy three percent of the totals, suggestive of medium quality of QWL. Older with longer job experience, having higher salary and poorly educated workers showed significantly higher QWL score (p<0.01). They seem content with their work life and are satisfied in their job. Food and nutrient intakes were inadequate both in quality and quantity. Mean calorie intake was 2196 ± 400 kcal (79% RDI). Cereals and roots/tubers were the major contributor of energy (65% of the total) and protein consumed. Intakes of egg, meat and milk products were very poor. About twenty percent of the workers measured undernourished (BMI<18.5). Moderate level of QWL compounded with poor and inadequate nourishment would certainly compromise work performance and thereby contribute to low productivity.